Mewujudkan Transisi yang Lancar: Strategi Menarik dalam Mendukung Anak Menuju SD dari PAUD - indah Pebriani; Kinda Handayani (AGUSPATI RESEARCH INSTITUTA, 2024)
This research aims to eliminate the calistung test from the process of admitting new students to elementary school. Implement an introductory period for new students during the first two weeks (in PAUD and SD). Implementing learning that builds six foundational abilities of children (in PAUD and SD). The Fun Transition Movement from PAUD to SD is a joint movement that underlies the transition of PAUD students to SD/MI/equivalent in a fun way and starts from the new school year. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from the KEMDIKBUD RI YouTube channel entitled